PROFESSIONAL ETHICS OF TEACHER IN THE EDUCATIONAL PROCESS - Shaymanova Yulduz Toshniyazovna (International Engineering Journal For Research & Development, 2022)
The article discusses professional ethics and its specific aspects. In the process of teaching, information is provided on the issues of teacher skills and its specific aspects. The fact that a teacher has a great deal of knowledge and experience in shaping students ’abilities and interests is analyzed with a number of examples. It is clear that every professional needs to inculcate the essence of professional ethics in the minority.